2021
DOI: 10.1371/journal.pone.0256446
|View full text |Cite
|
Sign up to set email alerts
|

High risk of burnout in medical students in Serbia, by gender: A cross-sectional study

Abstract: Introduction Burnout syndrome is common among medical students, but findings about the gender differences in burnout are not consistent. The aim of this study was to assess high risk of burnout syndrome among medical students at one University in Serbia, by gender. Method A cross-sectional study was conducted at the Faculty of Medical Sciences, University of Kragujevac in 2014. The Maslach Burnout Inventory—Student Survey was used for assessment of burnout level. A questionnaire on basic socio-demographic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…Furthermore, our study found that only female medical undergraduates showed strong association between alcohol abuse/dependence and learning burnout. This was consistent with findings of other studies, which showed a significant association between the habit of drinking once or twice a week and burnout in female medical students only [ 81 ]. Notably, although a significantly higher prevalence of learning burnout was observed in male rather than female medical undergraduates, which was consistent with other studies [ 81 83 ], no significant association was found between alcohol abuse/dependence and learning burnout among male students.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our study found that only female medical undergraduates showed strong association between alcohol abuse/dependence and learning burnout. This was consistent with findings of other studies, which showed a significant association between the habit of drinking once or twice a week and burnout in female medical students only [ 81 ]. Notably, although a significantly higher prevalence of learning burnout was observed in male rather than female medical undergraduates, which was consistent with other studies [ 81 83 ], no significant association was found between alcohol abuse/dependence and learning burnout among male students.…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with findings of other studies, which showed a significant association between the habit of drinking once or twice a week and burnout in female medical students only [ 81 ]. Notably, although a significantly higher prevalence of learning burnout was observed in male rather than female medical undergraduates, which was consistent with other studies [ 81 83 ], no significant association was found between alcohol abuse/dependence and learning burnout among male students. This might be due to the gender difference in motivations for drinking, e.g., women were more likely to drink due to coping issues while men were more likely to drink for social and recreational reasons [ 84 , 85 ].…”
Section: Discussionsupporting
confidence: 93%
“…As for the higher burnout risk in male students with lower GPA (≤8), literature reports controversial findings ( 36 , 40 43 ). In our earlier report on the same sample of students analysing gender differences in burnout risk ( 29 ), we found no difference in GPA between genders (GPA>8 was self-reported by 62.8 % of males and by 64.2 % of females, P=0.716), but high burnout risk prevailed significantly in male than female students (19.0 % versus 12.8 %, respectively, P=0.024). However, these findings should also be taken with reserve, as the male and female groups did not match (491 female vs 269 male students in the total sample).…”
Section: Discussionmentioning
confidence: 49%
“…However, to the best of our knowledge, studies looking for associations between GPA and other characteristics of medical students (such as gender, habits, housing, and study financing) and the impact of these associations on burnout are relatively scarce. In our earlier study (29) analysing gender differences in burnout risk among medical students in Kragujevac, Serbia, we found no difference in GPA between genders (GPA>8 was self-reported by 62.8 % of males and by 64.2 % of females, P=0.716), but high burnout risk significantly prevailed in male than female students (19.0 % versus 12.8 %, respectively, P=0.024). The aim of this study, however, was to look deeper and assess in the same sample of students how burnout may affect academic performance in view of other factors associated with it.…”
mentioning
confidence: 70%
See 1 more Smart Citation